Differences in Physiological Characteristics and Heat Shock Protein Expression in Taiwan Swamp Buffaloes During Winter and Summer Seasons - Chen, Pei Chung; Chuang, Pi Hua; Dai, Bing Rong; Chang, Ching Wei; Wei, Liang Yuan (Journal of Buffalo Science, 2025)
Background: This study examined the respiratory rate, rectal temperature, and expression levels of heat shock protein 70 (HSP70) and heat shock protein 90 (HSP90), as revealed by ELISA, in Taiwan swamp buffaloes (Bubalus bubalis, swamp-type) during the winter (February) and summer (August) seasons of 2022 in Taiwan. Methods: Data were collected from Taiwan swamp buffaloes during the winter and summer seasons. Respiratory rate, rectal temperature, and protein expression levels were measured and analyzed. Results: The results revealed age-related differences in response to changes in environmental temperature. In winter, buffaloes aged <1 year exhibited significantly higher respiratory rates, rectal temperatures, and heat tolerance coefficients than female buffaloes aged 14 to 20 years (P < 0.05). In the summer season, buffaloes aged <1 year had significantly higher rectal temperatures (P < 0.05) and higher expression levels of HSP70 (from ELISA) than female buffaloes aged 6 to 9 years and 14 to 20 years (P < 0.05). Conclusion: The findings suggest that the age of Taiwan swamp buffaloes affects their physiological responses to heat stress, with younger buffaloes exhibiting greater physiological reactions to heat stress than older buffaloes.